Review of the Effectiveness of Article 76 C of Law Number 35 of 2014 concerning Child Protection in the Prevention and Eradication of Bullying in Indonesia - Safrilla Ayu Maharani; Nu’man Aunuh; Cholidah (Faculty of Law, Universitas Pekalongan, 2025)
Bullying is a negative action that is carried out repeatedly by a stronger or powerful individual against a weaker individual. Article 76C of Law Number 35 of 2014 concerning Child Protection prohibits everyone from placed, allowing, doing, ordering to do, or participating in violence against children. This provision aims to provide comprehensive protection for children from various forms of violence, including bullying. Although normatively Article 76C has regulated the prohibition of violence against children, implementation in preventing and eradicating bullying in Indonesia still faces various challenges. This study uses a normative juridical law research method that focuses on the study of applicable legal norms and their application in practice in society. These findings highlight the effectiveness of article 76C of law number 35 of 2014 concerning child protection in the prevention and eradication of bullying in Indonesia and how the ideal legal concept is in order to reduce bullying in Indonesia.